2020
DOI: 10.1186/s12979-020-00183-z
|View full text |Cite
|
Sign up to set email alerts
|

The lethal sex gap: COVID-19

Abstract: While Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is disrupting lives across the globe for everyone, it has a more devastating impact on the health of older adults, especially that of older men. This pandemic has highlighted the crucial importance of considering an individual's age and biological sex in the clinic in addition to other confounding diseases (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 87 publications
8
89
0
3
Order By: Relevance
“…Other factors may be involved in infection such as hormone-regulated expression of genes or environmental factors like smoking, drinking and personal care [23]. Chronic activation of innate and adaptive immune functions increases with age and leads to a decline of the immune system response, causing a greater sensitivity to infections and chronic diseases [24].…”
Section: Analysis Of Infection Incidence In Exponential Virus Spreadingmentioning
confidence: 99%
“…Other factors may be involved in infection such as hormone-regulated expression of genes or environmental factors like smoking, drinking and personal care [23]. Chronic activation of innate and adaptive immune functions increases with age and leads to a decline of the immune system response, causing a greater sensitivity to infections and chronic diseases [24].…”
Section: Analysis Of Infection Incidence In Exponential Virus Spreadingmentioning
confidence: 99%
“…At the time of writing this paper, late July 2020, there have been 16.34 m confirmed cases and 650,805 deaths [5]. Being male has been shown to be a particular risk factor for developing the severe form of the disease and mortality [2,[6][7][8][9][10]. A modeling exercise on the possibility of developing severe COVID-19 as a result of underlying health conditions suggests that 6% (225 m) of the global male population may be at risk of requiring hospital admission if infected (3%/123 m females) [11].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of the disease appears similar between sexes, however men with Covid-19 are more at risk for worse outcomes and death compared to women, independent of age (Jin et al 2020). There is no fixed explanation for the age and sex distribution of Covid 19 but it has been observed that older age and male sex are independently related to changes in the performance of the immune system with a decline in adaptive immunity, mainly of Treg lymphocytes, paralleled by an activation of innate immunity and this resembles what is seen in Covid 19 (Márquez et al 2020).…”
Section: Age and Sex Ratio Of Covid 19mentioning
confidence: 97%